A prospective evaluation to define optimal surgical strategies in the management of complex pancreatic injuries based on the analysis of patients treated at a major South African academic institution - Krige, Jacobus Edmund Joubert (Department of Surgery, 2018)
In order to address crucial existing limitations in the assessment and analysis of pancreatic injuries due to the lack of robust data and deficient surgical strategies, this thesis focused on priority topics to resolve existing unanswered and under-researched questions in the management of complex pancreatic injuries. Each of the twelve clinical studies in this thesis evaluated a specific aspect of pancreatic trauma based on the detailed analysis of prospective granular data from a large cohort of patients treated in an academic surgery and trauma centre with substantial experience in civilian operative trauma care in which standard and uniform protocols were applied.